2018
DOI: 10.18632/oncotarget.25834
|View full text |Cite
|
Sign up to set email alerts
|

Integration of stereotactic radiotherapy in the treatment of metastatic colorectal cancer patients: a real practice study with long-term outcome and prognostic factors

Abstract: BackgroundThere are very few clinical or prognostic studies on the role of SRT (Stereotactic Radiation Therapy) in the continuum of care of metastatic colorectal cancer (mCRC) patients.Patients and methodsPatients affected by oligo-mCRC were treated with SRT before or after front-line standard treatments. SRT was delivered according to a risk-adapted protocol. Total body CT (Computed Tomography) scan was done before therapy and every three months thereafter. The radiologic responses to therapy were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 35 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…19,23,[25][26][27][28] Total number of metastases treated with SABR was not a clear prognostic factor according to our analysis. Limited number (< 3) of metastases improved LC in one study 29 and OS in two. 22,28 In a retrospective study LC was significantly better for pulmonary oligometastases from rectal cancer compared to those from colon cancer.…”
Section: Sabr-related Predictors Of Response In Primary Tumor-specific Oligometastatic Disease Colorectal Cancermentioning
confidence: 90%
See 4 more Smart Citations
“…19,23,[25][26][27][28] Total number of metastases treated with SABR was not a clear prognostic factor according to our analysis. Limited number (< 3) of metastases improved LC in one study 29 and OS in two. 22,28 In a retrospective study LC was significantly better for pulmonary oligometastases from rectal cancer compared to those from colon cancer.…”
Section: Sabr-related Predictors Of Response In Primary Tumor-specific Oligometastatic Disease Colorectal Cancermentioning
confidence: 90%
“…Furthermore, Jingu et al showed in multivariate analysis that chemotherapy after SABR improved LC in pulmonary oligometastatic disease from CRC. 17 29 Li et al reported a correlation between radiological response to CT-scan and OS after SABR. The first radiology evaluation was at a median time of 1.8 months (0.5-8.0, range) and the second at 5.3 months (1.9-12.5, range).…”
Section: Sabr-related Predictors Of Response In Primary Tumor-specific Oligometastatic Disease Colorectal Cancermentioning
confidence: 99%
See 3 more Smart Citations